Identifying the Main Drivers of Productivity Growth A Literature Review (OECD Publishing, 2022)
This report represents the second outcome of the collaboration between the Asian Productivity Organization (APO) and the Organisation for Economic Co-operation and Development (OECD) to improve the measurement and analysis of productivity developments across APO and OECD member economies. The report discusses the potential impact of COVID-19 on productivity and examines the role of Multifactor Productivity (MFP) as a major driver of economic growth and changes in living standards. It then identifies the most important factors influencing MFP growth and describes the most important challenges affecting the measurement of each of these factors as well as the estimation of their impact on MFP. The report provides key recommendations to improve the reliability and interpretation of the empirical evidence for economic analysis